2011
DOI: 10.1161/atvbaha.111.226373
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Platelet Activation at Medically Used Hypothermia and Mechanistic Data Indicating ADP as a Key Mediator and Therapeutic Target

Abstract: Objective-Hypothermia is used in various clinical settings to inhibit ischemia-related organ damage. However, prothrombotic effects have been described as potential side effects. This study aimed to elucidate the mechanism of hypothermia-induced platelet activation and subsequent prothrombotic events and to develop preventative pharmacological strategies applicable during clinically used hypothermia. Methods and Results-Platelet function was investigated ex vivo and in vivo at clinically used hypothermia (28°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 56 publications
0
44
0
4
Order By: Relevance
“…Prior prospective studies investigating hypothermia during primary PCI have not reported stent thrombosis rates. Hypothermia increases platelet activation, which directly contributes to thrombosis 26 and, in addition, may attenuate the efficacy of ADP antagonists. 27,28 Hypothermia may also induce cholesterol crystallization, which could trigger plaque rupture.…”
Section: Results Of the Current Study: Safetymentioning
confidence: 99%
“…Prior prospective studies investigating hypothermia during primary PCI have not reported stent thrombosis rates. Hypothermia increases platelet activation, which directly contributes to thrombosis 26 and, in addition, may attenuate the efficacy of ADP antagonists. 27,28 Hypothermia may also induce cholesterol crystallization, which could trigger plaque rupture.…”
Section: Results Of the Current Study: Safetymentioning
confidence: 99%
“…These guidelines recommend that blood preparation should be carried out at room temperature and variations in temperature should be avoided due to the activation of blood cells at decreased temperatures [83,84]. However, there is evidence to suggest that a temperature of 37°C, constantly kept during the blood withdrawal, storage and preparation as well as during the final assay, may reflect the in vivo situation even more appropriately [85][86][87].…”
Section: Hemocompatibility Testingmentioning
confidence: 99%
“…PRP was incubated with PBS (vehicle control) or rsol.CD39-PSGL-1 (150-450 ng; purified from conditioned media) at 37°C for 30 min. Platelet aggregation in the presence of agonists ADP and collagen were studied using the AggRAMTM System, Helena Laboratories, Beaumont, TX, USA, as published [19].…”
Section: Methodsmentioning
confidence: 99%
“…Warm renal IRI model 10-to 14-week-old male mice were subjected to warm, unilateral kidney IRI surgery as described previously [19]. Briefly, following anaesthesia with xylazine ketamine, mice were placed on a 37°C heating pad and their core body temperature was maintained for the duration of the surgery.…”
Section: Methodsmentioning
confidence: 99%